The role of strategic leadership in achieving organizational excellence: field research in Al-Faris General Company - نادر, علاء محمد; جاسم, باسم عبد الحسن (Journal of Economics and Administrative Sciences, 2019)
The current research aims to determine the role of strategic leadership in achieving organizational excellence. In this context the sample of the research consist of 123 managers .The research problem can be summarized as {what is the role of strategic leadership in achieving organizational excellence}which resulted in a number of sub-questions and its goal was to explain the theoretical philosophy and intellectual expositions of this variables because of they are vital variables imposed by the current situation. To achieve research objectives we had use the questionnaire as a tool to collect data and information after verifying the validity and dependency of the measures. A number of statistical techniques and tools had been used to prove the validity of research hypothesis such as(arithmetic mean ,standard deviation , correlation, and linear regression) . The research conclude to a number of specific conclusions among the most important of which is that the strategic leadership is positively related with organizational excellence. A set of recommendations was formulated that we hope it would be useful to those who is interested.